Patient recovery after Lisfranc injury - Cezar Mucileanu; Andrei Agapi; Marius Turnea; Mariana Rotariu; Iustina Condurache (Balneo and PRM Research Journal, 2024)
Lisfranc joint injuries occur most frequently following road accidents, but also in military per-sonnel, athletes, horse riders, football players and contact sports participants. Lisfranc injuries occur as a result of direct (crushing the leg by a blunt object) or indirect (twisting the leg) forces acting on the forefoot. Approximately 20% of Lisfranc injuries go unnoticed or are diagnosed late, especially low-energy injuries or purely ligamentous injuries. Severe sequelae such as post-traumatic osteoarthritis and foot deformities can create serious disability. The paper presents a 19-year-old male patient, diagnosed with a Lisfranc type lesion in the left leg. The patient was functionally assessed postoperatively, during and at the end of the recovery program. During the recovery program, a good progress and evolution of the patient could be observed. Thus, the patient followed the kinetic program initially established by the physical therapist, and it was also possible to observe the increase in joint mobility, stability and muscle strength. The physical therapy program designed must be preceded by an appropriate assessment and must include techniques adapted to the patient's abilities. An essential condition is a good col-laboration between the patient-physiotherapist-orthopedic surgeon, so that complications and relapses can be avoided.